2014
DOI: 10.1371/journal.pone.0095970
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagic Flux by Salinomycin Results in Anti-Cancer Effect in Hepatocellular Carcinoma Cells

Abstract: Salinomycin raised hope to be effective in anti-cancer therapies due to its capability to overcome apoptosis-resistance in several types of cancer cells. Recently, its effectiveness against human hepatocellular carcinoma (HCC) cells both in vitro and in vivo was demonstrated. However, the mechanism of action remained unclear. Latest studies implicated interference with the degradation pathway of autophagy. This study aimed to determine the impact of Salinomycin on HCC-autophagy and whether primary human hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 37 publications
(64 reference statements)
1
56
0
Order By: Relevance
“…SAL was reported to induce cell death via autophagy upregulation in some experimental models [45, 46]. However, it was recently reported that 2 μM SAL inhibits the autophagic flux in breast and hepatocellular carcinomas [43, 47]. In order to establish the activity of SAL on autophagic flux, we started our investigation by using HOS cells stably transfected with a GFP-LC3 vector, which allows the analysis of the autophagic flux by flow cytometry by monitoring the accumulation of GFP-LC3-positive autophagosomes in the presence of lysosomal inhibitors [48].…”
Section: Resultsmentioning
confidence: 99%
“…SAL was reported to induce cell death via autophagy upregulation in some experimental models [45, 46]. However, it was recently reported that 2 μM SAL inhibits the autophagic flux in breast and hepatocellular carcinomas [43, 47]. In order to establish the activity of SAL on autophagic flux, we started our investigation by using HOS cells stably transfected with a GFP-LC3 vector, which allows the analysis of the autophagic flux by flow cytometry by monitoring the accumulation of GFP-LC3-positive autophagosomes in the presence of lysosomal inhibitors [48].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, salinomycin was demonstrated to be an mTOR C1 and Wnt/b-catenin signaling inhibitor by suppressing lipoprotein receptor-related protein-6 (LRP6) in breast and prostate cancer cells (Lu and Li, 2014). Another study showed an inhibition of autophagic activity by salinomycin in hepatocellular carcinoma (Klose et al, 2014). Additionally, salinomycin was introduced as a potent drug to overcome apoptosis resistance in several types of cancer (Lieke et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sal was dissolved in dimethyl sulfoxide (DMSO) for in vitro analysis [16] or in corn oil for in vivo applications [17]. 5-FU was dissolved in phosphate buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were analyzed for apoptosis, late apoptosis or necrosis induction following exposure to either Sal or 5-FU alone or combined Sal and 5-FU for 24 h applying the AnnexinV apoptosis detection kit (BD Biosciences) according to the manufacturer’s instructions as previously described [16, 23]. AnnexinV positive cells were regarded as apoptotic cells; AnnexinV/PI positive cells were regarded as late apoptotic and PI positive cells were regarded as necrotic cells.…”
Section: Methodsmentioning
confidence: 99%